Propuesta de un video didáctico animado en 3D, sobre el funcionamiento del sistema digestivo humano, para la aplicación de un programa piloto en el canal 8 Ecuavisa - Borja Miranda, Jorge Andrés (2012)
3D animation is a discipline within the field of computing that allows characters to life through inanimate tools and techniques of traditional animation to date in a digital environment. Therefore, it is currently one of the best digital techniques. In the television program "Towards a new style" of life is being used as 2D animation tool for the visualization of medical issues, but in order to engage the new technology used by Ecuavisa, we have considered the use of 3D tool. With this animation tool is expected to the methodology used to explain the health issue, more educational, fun and interactive, according to the new technology. "Towards a new lifestyle," is an Ecuadorian television program that airs on ECUAVISA, which addresses issues of preventive and curative medicine….